Aluminum-based lithium ion battery lithium supplementing additive, preparation method and application thereof

CN122889867APending Publication Date: 2026-10-09TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611331297.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

[0018]在匀浆过程中,将补锂添加剂与所使用的正极材料LiNi0.6Co0.1Mn0.3O2同时加入匀浆瓶中搅拌制备正极。采用上述正极补锂添加剂Li5+xAl1-xMnxO4(其中x满足0.05≤x≤0.2)对锂离子电池进行补锂,进而提高锂离子电池能量密度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889867A_ABST
    Figure CN122889867A_ABST
Patent Text Reader

Abstract

The application discloses an aluminum-based lithium ion battery lithium supplementing additive and a preparation method and application thereof. The chemical formula of the aluminum-based lithium ion battery lithium supplementing additive is Li 5+x Al 1‑x Mn x O4 (wherein 0.05<=x<=0.2, preferably Li 5.1 Al 0.9 Mn 0.1 O4) belongs to an orthorhombic system and has a derivative reverse-fluorite structure of a Pmmn space group. A lithium source, aluminum oxide and manganese oxide are uniformly mixed according to a stoichiometric ratio to form a mixture; the mixture is placed in a tube furnace and heated to 750-1000 DEG C under a protective atmosphere, and is kept for 10-30 hours for reaction, and the positive electrode lithium supplementing additive is obtained through the reaction. The positive electrode lithium supplementing additive prepared by the application has the advantages of small particle size, delicate material morphology, uniform distribution and high charge specific capacity, and can be applied to a positive electrode slurry and a battery to effectively compensate for irreversible loss of active lithium caused by formation of a solid electrolyte interface film in a first charge-discharge process, significantly improve the first coulombic efficiency and energy density of the lithium ion battery, and effectively inhibit generation of byproduct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery cathode lithium replenishment materials. Specifically, it relates to a lithium-ion battery lithium replenishment additive for cathode, its preparation method, and its application in lithium-ion batteries. Background Technology

[0002] With the rapid development of electric vehicles, portable electronic devices, and large-scale energy storage systems, the market has placed higher demands on the energy density, cycle life, and safety performance of lithium-ion batteries. However, during the first charge of a lithium-ion battery, a solid electrolyte interphase (SEI) film spontaneously forms on the surface of the negative electrode, irreversibly consuming a large amount of active lithium from the positive electrode. Especially when a silicon-based negative electrode with extremely high theoretical capacity is introduced, its massive volume expansion and material properties lead to a significant reduction in the initial coulombic efficiency, resulting in severe irreversible lithium loss. This "dead lithium" phenomenon drastically reduces the actual usable capacity and energy density of the battery.

[0003] To compensate for the loss of inactive lithium, lithium replenishment technology (pre-lithiation) has emerged. Compared to negative electrode lithium replenishment (such as using lithium metal powder, lithium foil, etc., which poses safety hazards and has extremely high process requirements), positive electrode lithium replenishment technology directly mixes high-capacity lithium replenishment additives into the positive electrode slurry during the slurry mixing stage, which has significant advantages such as good compatibility with existing battery production processes and safer operation.

[0004] Currently, commonly used cathode lithium replenishment additives mainly include lithium-rich transition metal oxides (such as Li5FeO4 and Li6CoO4) and anti-fluorite structure compounds (such as Li2O and Li2O2). However, existing cathode lithium replenishment additives all produce byproducts after the first cycle. For example, Li5FeO4 produces Fe2O3 after cycling, and Li6CoO4 produces Co2O3. The residual Fe2O3 and Co2O3 byproducts after delithiation can react with the electrolyte, leading to electrolyte decomposition or cathode surface passivation, increasing the impedance at the cathode-electrolyte interface. Furthermore, Li2O and Li2O2 produce a large amount of O2 after the first cycle. The accumulation of this gas not only causes severe battery swelling and damages the tight contact interface between the electrodes, causing a surge in internal resistance, but the highly reactive oxygen also easily oxidizes the electrolyte, leading to a serious risk of thermal runaway.

[0005] Therefore, developing a highly safe cathode lithium supplement additive that can provide high lithium replenishment capacity while suppressing gas generation, eliminating harmful inert residues and transition metal dissolution is a key issue that the industry urgently needs to address. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide an aluminum-based lithium-ion battery lithium replenishment additive, its preparation method and application, so as to at least improve the energy density of lithium-ion batteries and suppress the generation of by-reaction products.

[0007] To address the above technical problems, an aluminum-based lithium-ion battery lithium replenishment additive is provided according to one aspect of the present invention, the chemical formula of which is Li. 5+x Al 1-x Mn x O4, where 0.05 ≤ x ≤ 0.2, this material is a manganese (Mn)-doped high-temperature Li5AlO4-based solid solution with a derived antifluorite structure of the Pmmn space group. By introducing a specific proportion of manganese (Mn) heteroatoms into the Li5AlO4 derived antifluorite framework, the high symmetry of the Pmmn space group crystal structure is maintained, while the manganese (Mn) heteroatoms promote lithium-ion extraction to achieve a lithium replenishment effect. This high-temperature phase structure endows the material with high chemical stability.

[0008] According to another aspect of the present invention, a method for preparing the above-described aluminum-based lithium-ion battery lithium replenishment additive is provided, the specific steps of which include: (1) The lithium source, aluminum oxide and manganese oxide are mixed uniformly according to the stoichiometric ratio to obtain a mixture; (2) The mixture is placed in a tube furnace and heated to 750~1000 °C under a protective atmosphere (inert atmosphere or reducing atmosphere) and kept at the temperature for 10~30 h to obtain the positive electrode lithium supplementation additive.

[0009] In a preferred embodiment, the lithium source is selected from at least one of anhydrous LiOH, LiOH×H2O, and Li2CO3.

[0010] In a preferred embodiment, the aluminum oxide is Al2O3.

[0011] In a preferred embodiment, the manganese oxide is MnO.

[0012] In a preferred embodiment, the inert atmosphere is Ar or N2.

[0013] In a preferred embodiment, the reducing atmosphere is an H2 / Ar mixture.

[0014] As a preferred embodiment, in step (2), the temperature is raised to 950 °C and the reaction is maintained for 20 h.

[0015] According to another aspect of the present invention, the application of the above-mentioned aluminum-based lithium-ion battery lithium replenishing additive in the preparation of lithium-ion batteries is provided.

[0016] According to another aspect of the present invention, a lithium-ion battery positive electrode slurry is provided, the positive electrode slurry comprising a positive electrode active material and the above-mentioned positive electrode lithium supplementation additive, wherein the positive electrode lithium supplementation additive accounts for 5 to 10% of the total mass of the positive electrode slurry.

[0017] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet containing the aforementioned aluminum-based lithium-ion battery lithium replenishment additive, or prepared by coating the aforementioned positive electrode slurry onto the surface of a positive electrode current collector.

[0018] During the homogenization process, the lithium supplementation additive is mixed with the cathode material LiNi. 0.6 Co 0.1 Mn 0.3 O2 was simultaneously added to the homogenizing bottle and stirred to prepare the positive electrode. The aforementioned lithium-added additive for the positive electrode, Li... 5+x Al 1-x Mn x O4 (where x satisfies 0.05≤x≤0.2) is used to replenish lithium in lithium-ion batteries, thereby improving the energy density of lithium-ion batteries.

[0019] This invention utilizes different primary lithium source materials, such as anhydrous LiOH, LiOH×H2O, and Li2CO3, to generate the positive electrode lithium replenishment material Li. 5+x Al 1-x Mn x The material prepared by O4 (where x satisfies 0.05≤x≤0.2) has a fine particle size, delicate morphology, and uniform distribution, and has significant advantages such as high charging specific capacity.

[0020] This invention effectively avoids the irreversible loss of active lithium caused by the formation of the solid electrolyte interface (SEI) and suppresses the generation of by-reaction products.

[0021] This invention employs a high-temperature thermal reduction method, through lithium addition and high-temperature calcination, to generate Li from a lithium source, aluminum oxide, and manganese oxide. 5+x Al 1-x Mn x O4 (where x satisfies 0.05≤x≤0.2) is prepared using a simple and easy-to-implement method that allows for precise and controllable lithium replenishment. It is also low in cost, highly reproducible, and compatible with existing lithium-ion battery production processes, requiring no additional steps. Attached Figure Description

[0022] Figure 1 Li prepared in Example 1 5.05 Al 0.95 Mn 0.05 SEM image of O4 lithium supplement additive.

[0023] Figure 2 Li prepared in Example 25.1 Al 0.9 Mn 0.1 Figure 1 shows the first charge and discharge cycle of a half-cell with O4 lithium supplementation additive.

[0024] Figure 3 Li prepared in Example 1 5.05 Al 0.95 Mn 0.05 Comparison of the first charge and discharge cycles of half-cells with ordinary cathode materials after O4 lithium supplementation additive was added to the cathode material.

[0025] Figure 4 Li prepared in Example 2 5.1 Al 0.9 Mn 0.1 Comparison of the first charge and discharge cycles of a full battery with O4 lithium supplement additive added to the cathode material and a battery with ordinary cathode material.

[0026] Figure 5 Li prepared in Example 3 5.15 Al 0.85 Mn 0.15 Comparison of the first 100 half-cell cycles between the addition of O4 lithium supplementation additive to the cathode material and ordinary cathode material.

[0027] Figure 6 Li prepared in Example 4 5.2 Al 0.8 Mn 0.2 Comparison of the first 200 full-cell cycles between the addition of O4 lithium supplementation additive to the cathode material and ordinary cathode material.

[0028] Figure 7 Different mass fractions of Li were added to Examples 1 and 5. 5.1 Al 0.9 Mn 0.1 Comparison of the first charge and discharge of half-cells using O4 lithium supplementation additive cathode materials and ordinary cathode materials.

[0029] Figure 8 The images show the XRD patterns of the cathode lithium supplementation additives with different Mn doping ratios prepared in Examples 1-4. Detailed Implementation

[0030] The technical solutions claimed in this invention will be further described below through some embodiments. However, the embodiments and comparative examples are for explaining the implementation of the present invention and do not exceed the scope of the subject matter of the present invention. The scope of protection of the present invention is not limited by the embodiments. Unless otherwise specified, the materials and reagents used in this invention can be obtained from commercially available products in the art.

[0031] Example 1 (1) Anhydrous LiOH:Al2O3:MnO were mixed evenly in a molar ratio of 5.05:0.475:0.05 and ground in a mortar for 15 min to obtain a uniform mixture.

[0032] (2) The mixture was placed in a tube furnace and heated to 800 °C in a N2 atmosphere for 25 h. After natural cooling, the product Li was obtained. 5.05 Al 0.95 Mn 0.05 O4. The product was characterized by XRD and compared with a standard PDF card; the results are shown in the attached figure. Figure 8 As shown. The material is a pure phase, with no impurities generated.

[0033] (3) The product Li 5.05 Al 0.95 Mn 0.05 O4 is used as an additional positive electrode active material, according to LiNi 0.6 Co 0.1 Mn 0.3 O2: Li 5.05 Al 0.95 Mn 0.05 The O4:Super-P:PVDF ratio of 76:4:10:10 was stirred and mixed evenly to form a slurry. The slurry was then coated onto aluminum foil using a coating machine to form an electrode sheet. The electrode sheet was then baked in an 80 ℃ oven for 10 h and then baked in a 120 ℃ vacuum oven for 8 h.

[0034] (4) Cut the positive electrode sheet with a diameter of 12 mm, assemble the half cell, and test it under the Blue Electric Test System at a voltage of 3-4.3 V and a first cycle of 0.1C.

[0035] Under the same conditions, prepare Li-free 5.05 Al 0.95 Mn 0.05 Ordinary LiNi O4 0.6 Co 0.1 Mn 0.3 O2 positive electrode sheets were assembled into a full cell as a control and tested under the same conditions.

[0036] like Figure 3 As shown, add Li 5.05 Al 0.95 Mn 0.05 After O4, the specific charging capacity of the battery decreased from 200.3 mAh g. −1 Increased to 206.6 mAh g −1 The specific discharge capacity increased from 152.6 mAh g. −1 Increased to 158.5 mAh g −1 .

[0037] Example 2 (1) Anhydrous LiOH:Al2O3:MnO were mixed evenly in a molar ratio of 5.1:0.45:0.1 and ground in a mortar for 15 min to obtain a uniform mixture.

[0038] (2) The mixture was placed in a tube furnace and heated to 950 °C in an Ar atmosphere for 20 h. After natural cooling, the product Li was obtained. 5.1 Al 0.9 Mn 0.1 O4. The product was characterized by XRD and compared with a standard PDF card; the results are shown in the attached figure. Figure 8 As shown. The material is a pure phase, with no impurities generated.

[0039] (3) The product Li 5.1 Al 0.9 Mn 0.1 O4, as a standalone cathode material, follows the Li 5.1 Al 0.9 Mn 0.1 O4:Super-P:PVDF = 30:20:10 by mass mixing to form a slurry. The slurry is then coated onto aluminum foil using a coating machine to form an electrode sheet. The electrode sheet is then baked in an 80 ℃ oven for 10 h and then in a 120 ℃ vacuum oven for 8 h.

[0040] (4) The product Li 5.1 Al 0.9 Mn 0.1 O4 is used as an additional positive electrode active material, according to LiNi 0.6 Co 0.1 Mn 0.3 O2: Li 5.1 Al 0.9 Mn 0.1 The O4:Super-P:PVDF ratio of 76:4:10:10 was stirred and mixed evenly to form a slurry. The slurry was then coated onto aluminum foil using a coating machine to form an electrode sheet. The electrode sheet was then baked in an 80 ℃ oven for 10 h and then baked in a 120 ℃ vacuum oven for 8 h.

[0041] (5) The graphite negative electrode homogenization process is basically the same as that of the positive electrode. The graphite negative electrode is mixed evenly according to the required mass ratio of GR:Super-P:PVDF=80:10:10 to form a slurry. The slurry is coated on copper foil using a coating machine to form an electrode sheet. The electrode sheet is placed in an 80 ℃ oven for 10 h and then placed in a 120 ℃ vacuum oven for 8 h.

[0042] (6) After cutting the positive and negative electrode sheets with a diameter of 12 mm, match the positive and negative electrode sides according to the N / P ratio of 1.1. After assembling the full cell, test it under the Blue Electric Test System with a voltage of 3-4.3 V and the first cycle at 0.1 C.

[0043] Under the same conditions, prepare Li-free 5.1 Al 0.9 Mn 0.1 Ordinary LiNi O4 0.6 Co 0.1 Mn 0.3 O2 positive electrode sheets were assembled into a full cell as a control and tested under the same conditions.

[0044] like Figure 4 As shown, add Li 5.1 Al 0.9 Mn 0.1 After O4, the specific charging capacity of the graphite full battery increased from 200.2 mAh g. −1 Increased to 206.3 mAh g −1 The specific discharge capacity increased from 145.3 mAh g. −1 Increased to 157.7 mAh g −1 .

[0045] Example 3 (1) Mix Li2CO3:Al2O3:MnO in a molar ratio of 2.575:0.425:0.15 until homogeneous, and grind in a mortar for 15 min to obtain a homogeneous mixture.

[0046] (2) The mixture was placed in a tube furnace and heated to 1000 °C in a mixed reducing atmosphere of 5% H2 + 95% Ar by volume. The temperature was maintained for 10 h, and the product Li was obtained after natural cooling. 5.15 Al 0.85 Mn 0.15 O4. The product was characterized by XRD and compared with a standard PDF card; the results are shown in the attached figure. Figure 8 As shown. The material is a pure phase, with no impurities generated.

[0047] (3) The product Li 5.15 Al 0.85 Mn 0.15 O4 is used as an additional positive electrode active material, according to LiNi 0.6 Co 0.1 Mn 0.3 O2: Li 5.15 Al 0.85 Mn 0.15The O4:Super-P:PVDF ratio of 76:4:10:10 was stirred and mixed evenly to form a slurry. The slurry was then coated onto aluminum foil using a coating machine to form an electrode sheet. The electrode sheet was then baked in an 80 ℃ oven for 10 h and then baked in a 120 ℃ vacuum oven for 8 h.

[0048] (4) Cut the positive electrode sheet with a diameter of 12 mm, assemble the half cell, and test it under the Blue Electric Test System with a voltage of 3-4.3 V, 0.1 C for the first 10 revolutions and 1 C for the next 90 revolutions.

[0049] Under the same conditions, prepare Li-free 5.15 Al 0.85 Mn 0.15 Ordinary LiNi O4 0.6 Co 0.1 Mn 0.3 O2 positive electrode sheets were assembled into a full cell as a control and tested under the same conditions.

[0050] like Figure 5 As shown, add Li 5.15 Al 0.85 Mn 0.15 After O4, the cycle performance of the half-cell was significantly improved, with the capacity retention rate increasing from 69.2% to 74.1%.

[0051] Example 4 (1) Anhydrous LiOH:Al2O3:MnO were mixed evenly in a molar ratio of 5.2:0.4:0.2 and ground in a mortar for 15 min to obtain a uniform mixture.

[0052] (2) The mixture was placed in a tube furnace and heated to 750 °C in an Ar atmosphere for 30 h. After natural cooling, the product Li was obtained. 5.2 Al 0.8 Mn 0.2 O4. The product was characterized by XRD and compared with a standard PDF card; the results are shown in the attached figure. Figure 8 As shown. The material is a pure phase, with no impurities generated.

[0053] (3) The product Li 5.2 Al 0.8 Mn 0.2 O4 is used as an additional positive electrode active material, according to LiNi 0.6 Co 0.1 Mn 0.3 O2: Li 5.2 Al 0.8 Mn 0.2The O4:Super-P:PVDF ratio of 76:4:10:10 was stirred and mixed evenly to form a slurry. The slurry was then coated onto aluminum foil using a coating machine to form an electrode sheet. The electrode sheet was then baked in an 80 ℃ oven for 10 h and then baked in a 120 ℃ vacuum oven for 8 h.

[0054] (4) The graphite negative electrode homogenization process is basically the same as that of the positive electrode. The grout is stirred and mixed evenly according to the required mass ratio of GR:Super-P:PVDF=80:10:10 to form a slurry. The slurry is coated on copper foil using a coating machine to form an electrode sheet. The electrode sheet is placed in an 80 ℃ oven for 10 h and then placed in a 120 ℃ vacuum oven for 8 h.

[0055] (5) After cutting the positive and negative electrode sheets with a diameter of 12 mm, match the positive and negative electrode sides according to the N / P ratio of 1.1. After assembling the full cell, test it under the Blue Electric Test System with a voltage of 3-4.3 V, the first 10 cycles at 0.1 C and the next 190 cycles at 1 C.

[0056] Under the same conditions, prepare Li-free 5.2 Al 0.8 Mn 0.2 Ordinary LiNi O4 0.6 Co 0.1 Mn 0.3 O2 positive electrode sheets were assembled into a full cell as a control and tested under the same conditions.

[0057] like Figure 6 As shown. Add Li 5.2 Al 0.8 Mn 0.2 After O4, the cycle performance of graphite full cells is significantly improved, with the capacity retention rate of graphite full cells increasing from 72.0% to 83.7% after 200 cycles.

[0058] Example 5 The only difference from Example 2 is that the prepared LiNi 0.6 Co 0.1 Mn 0.3 O2: Li 5.1 Al 0.9 Mn 0.1 O4:Super-P:PVDF = 72:8:10:10 (mass ratio) were stirred until homogeneous to form a slurry. Testing was then conducted.

[0059] Under the same conditions, prepare Li-free 5.1 Al 0.9 Mn 0.1 Ordinary LiNi O4 0.6 Co 0.1 Mn0.3 O2 positive electrode sheets were assembled into half-cells as a control, and tested under the same conditions.

[0060] The measured results are as follows Figure 7 As shown, different proportions of Li were added: 5% and 10%. 5.1 Al 0.9 Mn 0.1 After O4, the specific charging capacity of the battery decreased from 202.6 mAh g. −1 Increased to 210.9 mAh g −1 and 231.1 mAh g −1 Add 5% Li 5.1 Al 0.9 Mn 0.1 After O4, the specific discharge capacity decreased from 159.3 mAh g. −1 Increased to 163.3 mAh g −1 Add 10% Li 5.1 Al 0.9 Mn 0.1 After O4, the specific discharge capacity decreased from 159.3 mAh g. −1 Slightly reduced to 153.6 mAh g −1 .

[0061] The materials prepared in the embodiments of this invention have fine particle size, delicate morphology, and uniform distribution, and do not affect the performance of the original cathode material. The SEM results are attached. Figure 1 As shown.

[0062] The positive electrode lithium replenishment additive prepared in this embodiment of the invention has a high lithium removal specific capacity, which can compensate for the lithium ions consumed during the first charge and discharge process of a lithium-ion battery due to the formation of a solid electrolyte interphase (SEI) film. The first charge and discharge results of the positive electrode lithium replenishment additive are shown in the attached figure. Figure 2 As shown.

[0063] Under the same active substance mass conditions, the present invention describes the addition of Li 5+x Al 1-x Mn x The cathode material of O4 (where x satisfies 0.05 ≤ x ≤ 0.2) is comparable to that without added Li. 5+x Al 1-x Mn x O4 (where x satisfies 0.05 ≤ x ≤ 0.2) cathode materials exhibit significant advantages such as high specific charging capacity. Furthermore, tests using half-cells with lithium foil as the anode and full-cells with graphite as the anode demonstrate that the addition of Li... 5+x Al 1-x Mn xThe initial charge specific capacity of the cathode material O4 (where x satisfies 0.05≤x≤0.2) is significantly improved, as shown in the attached figure. Figure 3 and attached Figure 4 As shown.

[0064] Furthermore, the synthesis method of this material is simple, easy to implement, and highly reproducible, matching existing lithium-ion battery production processes without requiring additional steps. Examples 1-4 of this invention synthesize Li+ cathode lithium supplementation additives with different Mn doping ratios. 5+x Al 1-x Mn x O4 (where x satisfies 0.05≤x≤0.2), using different lithium sources such as anhydrous LiOH, LiOH×H2O, and Li2CO3, mixed with aluminum-containing oxides and manganese-containing oxides, and then reacted at high temperature in a tube furnace under a protective atmosphere (inert or reducing atmosphere) to synthesize Li. 5+x Al 1-x Mn x O4 (where x satisfies 0.05 ≤ x ≤ 0.2), the four XRD results, after comparison with the PDF card, show that the synthesized materials are all pure phases, as shown in the attached figure. Figure 8 As shown.

Claims

1. An aluminum-based lithium-ion battery lithium replenishment additive, characterized in that, Its chemical formula is Li 5+x Al 1-x Mn x O4, where 0.05≤x≤0.2; the aluminum-based lithium-ion battery lithium replenishment additive belongs to the orthorhombic crystal system and has a derived antifluorite structure of the Pmmn space group.

2. A method for preparing an aluminum-based lithium-ion battery lithium replenishment additive as described in claim 1, characterized in that, Includes the following steps: (1) The lithium source, aluminum oxide and manganese oxide are mixed uniformly according to the stoichiometric ratio to obtain a mixture; (2) The mixture is placed in a tube furnace and heated to 750~1000 °C under a protective atmosphere. The mixture is kept at this temperature for 10~30 h to obtain the aluminum-based lithium-ion battery lithium replenishment additive.

3. The preparation method according to claim 2, characterized in that, The lithium source is selected from at least one of anhydrous LiOH, LiOH×H2O and Li2CO3.

4. The preparation method according to claim 2, characterized in that, The aluminum oxide mentioned is Al2O3.

5. The preparation method according to claim 2, characterized in that, The manganese oxide mentioned is MnO.

6. The preparation method according to claim 2, characterized in that, The protective atmosphere mentioned in step (2) is an inert atmosphere or a reducing atmosphere; preferably, the inert atmosphere is selected from Ar or N2, and the reducing atmosphere is a mixture of H2 / Ar gas.

7. The preparation method according to claim 2, characterized in that, In step (2), the temperature is raised to 950 °C and the reaction is maintained for 20 h.

8. The application of the lithium-ion battery positive electrode lithium replenishment additive as described in claim 1 in the preparation of lithium-ion batteries.

9. A lithium-ion battery positive electrode slurry, characterized in that, It includes a positive electrode active material and the aluminum-based lithium-ion battery lithium replenishing additive as described in claim 1, wherein the aluminum-based lithium-ion battery lithium replenishing additive accounts for 5-10% of the total mass of the positive electrode slurry.

10. A lithium-ion battery, comprising a positive electrode, characterized in that, The positive electrode sheet comprises the aluminum-based lithium-ion battery lithium supplementation additive as described in claim 1, or is prepared by coating the positive electrode slurry of the lithium-ion battery as described in claim 9 onto the surface of the current collector.